Technology-mediated education for marginalized populations: financial literacy gap - Jaya, Asri (Revenue Journal: Management and Entrepreneurship, 2023)
A person's financial attitude includes thoughts, attitudes, and self-confidence in managing money. A positive financial attitude is essential for responsible financial behavior and long-term well-being. Financial literacy includes financial behavior and consequences, not just information and skills. Technology in financial education has the potential to reduce the picture of financial literacy in developing countries. This research explains how technology-mediated financial education can be flexible, cost-effective, and adaptable, and reach communities underserved by financial services. This research also identified barriers such as inadequate infrastructure, limited access, and language and cultural barriers. Through extensive literature insights from various sources such as "ABInform", "EBSO Host", "Emerald", "Google Scholar", "Science Direct", "ProQuest", "Web of Science", and "ERIC", this research strives for digital inclusion and reduced financial literacy. The findings of this study suggest that although technology can be an effective tool, there is an urgent need for a thorough assessment of the long-term consequences and examination of comparative distribution techniques. This research emphasizes the need for further investigation to understand the impact of limited access to technology on financial literacy among marginalized communities.